Preference of halal eating culture ('Uruf) among Muslim community in Borneo - Jamaludin, Mohammad Aizat; Abd Rahman, Rusdy; Ab Rahman, Suhaimi; Ramli, Mohd Anuar; Yusoff, Halimatus Sa'diah (Yamani Angle Sdn Bhd, 2021)
Every culture in the country plays a different style and eating habit. They have their own uniqueness and preferences among the consumers. Different ethnics in Borneo own different taste and flavour of foods. The challenging of promoting halal foods to the consumers is due to lack of awareness among the consumers which leads to creating the obstacles in the aspects of selected foods and consuming foods. In corresponds to that, the alternatives are created to change the prohibited traditional foods to forbidden foods. The understanding of Islam can help in choosing the best foods